Design and Analysis of a New Excitation Structure for Magnetron Sputtering - Ze-da Su; Yue-Jun An; Hui An; Yan-Jun Lu; Wen-Yu Deng; Li-Jun Qi; Ming Li (IEEE Access, 2024)
Magnetron sputtering systems are widely used for depositing industrially important coatings. Research has been conducted to optimize and improve these structures to increase coating effectiveness and target utilization. The paper investigates the engineering problem of uneven target etching caused by an uneven magnetic field in magnetron sputtering equipment. The characteristics of the desired magnetic field distribution required by magnetron sputtering equipment are analyzed, and a corresponding excitation structure and analytical model for cylindrical magnetron sputtering equipment are proposed and calculated. The uniform magnetic field design is realized by analytical modeling of the excitation structure. The axial magnetic field distributions produced by an axisymmetric solenoid system and several similar excitation structures are analyzed and compared. The analytical results were verified through finite element simulations and experiments, demonstrating the accuracy and effectiveness of the method. The excitation structure, which is designed with a uniform magnetic field, can produce an axial component of magnetic flux density with a uniformity deviation of less than 4.3% across 73% of the target surface. The analytical model describes the distribution of the axial component of the magnetic flux density and optimizes the magnetic field. The model enables the simulation of plasma distribution and film growth, aiming to enhance the target utilization rate and substrate deposition rate. The conclusions serve as a reference for designing high-performance magnetron sputtering equipment.